Diphyllin Improves High-Fat Diet-Induced Obesity in Mice Through Brown and Beige Adipocytes - Duan, Ya-Nan; Ge, Xiang; Jiang, Hao-Wen; Zhang, Hong-Jie; Zhao, Yu; Li, Jin-Long; Zhang, Wei; Li, Jing-Ya (Frontiers in Endocrinology, 2020)
Brown adipose tissue (BAT) and beige adipose tissue dissipate metabolic energy and mediate nonshivering thermogenesis, thereby boosting energy expenditure. Increasing the browning of BAT and beige adipose tissue is expected to be a promising strategy for combatting obesity. Through phenotype screening of C3H10-T1/2 mesenchymal stem cells, diphyllin was identified as a promising molecule in brown adipocyte differentiation. In vitro studies revealed that diphyllin promoted C3H10-T1/2 cell and primary brown/beige preadipocyte differentiation and thermogenesis, which resulted in increased energy consumption. We synthesized the compound and evaluated its effect on metabolism in vivo. Chronic experiments revealed that mice fed a high-fat diet (HFD) with 100 mg/kg diphyllin had ameliorated oral glucose tolerance and insulin sensitivity and decreased body weight and fat content ratio. Adaptive thermogenesis in HFD-fed mice under cold stimulation and whole-body energy expenditure were augmented after chronic diphyllin treatment. Diphyllin may be involved in regulating the development of brown and beige adipocytes by inhibiting V-ATPase and reducing intracellular autophagy. This study provides new clues for the discovery of anti-obesity molecules from natural products